Glacial differences of Southern Ocean Intermediate Waters in the Central South Pacific. (15th March 2019) - Tapia, R.; Nürnberg, D.; Ho, S.L.; Lamy, F.; Ullermann, J.; Gersonde, R.; Tiedemann, R.
Abstract: Southern Ocean Intermediate Waters (SOIWs), such as Antarctic Intermediate Water and Subantarctic Mode Water, play a key role in modulating the global climate on glacial-interglacial time scales. They link the Southern Ocean and the tropics via mechanisms such as "oceanic tunneling" that transport climatic signals across latitudes. Despite their importance, the past evolution of the SOIWs in the Central South Pacific is largely unknown. Here we compare paired Mg/Ca-temperature, stable carbon (δ 13 C) and oxygen (δ 18 O) isotope records from surface-dwelling and deep-dwelling planktic foraminifera to infer changes in the water column structure for the last 260 ka in the Central South Pacific (54° S). Our study focuses on the subsurface oceanographic variability controlled by SOIWs, which are subducted at the Subantarctic Front. Our data show that the subsurface ocean in the Central South Pacific was colder and fresher during glacial stages than during the Holocene (0–10 ka BP), suggesting a general glacial enhanced presence of Antarctic Intermediate Water, in agreement with previous studies from the Eastern Equatorial Pacific and the Southeast Pacific. However, the subsurface ocean salinity differs for both glacial stages, with fresher condition during the Last Glacial Maximum (LGM; ∼26.5–19 ka BP) and more saline condition during the Penultimate Glacial Maximum (PGM; ∼155–140 ka BP). The δ 13 C data also show contrasting conditions for both glacial time windows in the upper water column, with a large depletion of 0.37‰ in δ 13 C from the LGM values, suggests a larger contribution of "old" low δ 13 C deep waters at intermediate depths at the study site during the PGM, plausibly due to stronger upwelling in high southern latitudes. The dissimilar scenarios between the LGM and the PGM may have been caused by processes that are analogous to the phase-switch in modern day Southern Annular Mode. Highlights: Colder and fresher subsurface waters during glacials in the Central South Pacific. Depth of source waters forming the AAIW in the CSP shifts between LGM and PGM. LGM-PGM conditions resemble the oceanographic changes caused by SAM.